2020
DOI: 10.1016/j.dib.2020.106209
|View full text |Cite
|
Sign up to set email alerts
|

Data describing child development at 6 years after maternal cancer diagnosis and treatment during pregnancy

Abstract: This manuscript is an accompanying resource of the original research article entitled “Child development at 6 years after maternal cancer diagnosis and treatment during pregnancy” and present data that compare the outcome of 6-year-old-children born to women diagnosed with cancer during pregnancy (with or without treatment during pregnancy) (study group) with children born after an uncomplicated pregnancy (control group). Oncological, obstetrical and neonatal data were collected. Neurodevelopment was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…A summary of the studies describing the type of maternal cancer and the chemotherapy schemes administered during pregnancy while evaluating the neurodevelopmental outcome of children in utero exposed to chemotherapy is demonstrated in Tables 1 and 2. [16] Acute leukemia (7) Non-Hodgkin's lymphoma (18) Hodgkin's lymphoma (14 Acute leukemia (14) Non-Hodgkin's lymphoma (25) Hodgkin's lymphoma (19) COPA (6 Breast cancer (26) Ovarian cancer (4) Hodgkin's lymphoma (4) Acute leukemia (1) [27] and Van Gerwen et al, 2020 [28] Breast cancer (69) Hematological malignancy (20) Cervical cancer 10Ovarian cancer (10) Brain cancer (4) Oral cavity and oropharyngeal cavity cancer 4Nasopharyngeal cancer (1) Gastric cancer 2Colon cancer 1Melanoma 2 Breast cancer and hematological cancer (e.g., acute leukemia, Hodgkin's lymphoma, non-Hodgkin's lymphoma) were the most frequently diagnosed malignancies during gestation [13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29]. Additionally, several cases of cervical, ovarian, brain and gastric cancer were also reported [13,14,[20][21][22]24,[26][27][28][29...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary of the studies describing the type of maternal cancer and the chemotherapy schemes administered during pregnancy while evaluating the neurodevelopmental outcome of children in utero exposed to chemotherapy is demonstrated in Tables 1 and 2. [16] Acute leukemia (7) Non-Hodgkin's lymphoma (18) Hodgkin's lymphoma (14 Acute leukemia (14) Non-Hodgkin's lymphoma (25) Hodgkin's lymphoma (19) COPA (6 Breast cancer (26) Ovarian cancer (4) Hodgkin's lymphoma (4) Acute leukemia (1) [27] and Van Gerwen et al, 2020 [28] Breast cancer (69) Hematological malignancy (20) Cervical cancer 10Ovarian cancer (10) Brain cancer (4) Oral cavity and oropharyngeal cavity cancer 4Nasopharyngeal cancer (1) Gastric cancer 2Colon cancer 1Melanoma 2 Breast cancer and hematological cancer (e.g., acute leukemia, Hodgkin's lymphoma, non-Hodgkin's lymphoma) were the most frequently diagnosed malignancies during gestation [13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29]. Additionally, several cases of cervical, ovarian, brain and gastric cancer were also reported [13,14,[20][21][22]24,[26][27][28][29...…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several cases of cervical, ovarian, brain and gastric cancer were also reported [13,14,[20][21][22]24,[26][27][28][29]. Some studies focused on a single type of pregnancy-related cancer analyzing its treatment along with the maternal and the fetal outcomes [15][16][17][18][23][24][25], whereas other studies integrated data regarding multiple cancer types, as shown in Table 1 [13,14,[20][21][22][26][27][28][29]. Furthermore, various chemotherapy regimens were administered during the course of pregnancy, depending on the type of maternal cancer diagnosed; a combination of anthracycline-based regimens was most commonly used [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations